PEMBELAJARAN SENI BUDAYA KELAS VIII E DI SMP NEGERI 3 PUNGGELAN - Galih Firmansah; Amrizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the limited availability of textile craft practice facilities, particularly copper batik stamp tools, at SMP Negeri 3 Punggelan. The relatively high cost of commercial batik stamps imposed a financial burden on students, resulting in suboptimal practice duration and limited creative opportunities for Grade VIII E students. As an innovative solution, waste paper from the school environment was utilized as an alternative medium to replace copper batik stamps, providing a more economical and environmentally friendly option. The objectives of this study were to describe the process of producing batik stamp tools from waste paper, to evaluate the functional quality of these tools, and to analyze the batik artworks produced by students using the alternative stamping media. This study employed a qualitative approach with a descriptive-analytical method. The research subjects consisted of 30 students from Class VIII E of SMP Negeri 3 Punggelan, Banjarnegara Regency. Primary data were collected through direct observation of the learning process, unstructured interviews with the principal, art and culture teacher, and students, as well as visual documentation of learning activities. Data analysis was conducted through data reduction, systematic data presentation, and conclusion drawing based on the frameworks of Constructivist Learning Theory, Art Product Theory, and Aesthetic Theory. The findings revealed that: (1) the process of producing batik stamp tools utilized thick waste paper (300–400 gsm) through stages of designing floral-geometric motif sketches, cutting paper strips, forming patterns according to the sketch outlines, and assembling layered stamp structures; (2) the functional quality evaluation indicated that waste paper-based batik stamps were economical, innovative, and sufficiently durable, as they were capable of absorbing and resisting dye liquids consistently; and (3) the analysis of students’ final batik products resulted in two classifications. The high-achievement groups (Groups 2 and 5) demonstrated superior performance in terms of pattern legibility, geometric precision, sharpness of double-line details, and cleanliness of color resistance. In contrast, the lower-achievement groups (Groups 1, 3, and 4) experienced technical problems, including dye bleeding effects and shape distortion caused by structural weaknesses of the stamping tools when subjected to repeated manual pressure. Overall, the utilization of waste paper proved effective as an alternative learning medium that was contextual, economical, environmentally friendly, and capable of fostering students’ ecological awareness in creating visual artworks.